The bitter principles of Tinospora rumphii Boerl. - De Guzman, Anita D.; Castillo, Amorita V. (Quezon City: College of Pharmacy, University of the Philippines, 1979.)
Extraction of the Makabuhay plant with various solvent systems was tried. A crude extract was obtained with ethanol as solvent. Although the presence of glycosides is indicated, work up on the crude extract failed to yield enough crystals for further study.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, October 1979.
Keywords: Menispermaceae; Makabuhay